2020
DOI: 10.3390/polym12030508
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Epoxy Modification of Bitumen: Modification Kinetics, Rheological Properties, and Microstructure

Abstract: Aiming to gain knowledge in the epoxy-bitumen modification mechanisms, this work explores the effects that epoxy concentration and ambient curing exert on the physico-chemistry and thermo-rheological properties of epoxy-modified binders. Process rheokinetics of epoxy-bitumen blends indicates that binder short-term modification (i.e., during processing) is accelerated by epoxy concentration. Furthermore, a synergistic effect of epoxy concentration and ambient curing is found during long-term modification (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 39 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have revealed that the penetration, ductility, and softening point are not able to characterize the rutting resistance performance index of asphalt under repeated vehicle loading [ 33 ]. In order to better evaluate the ability of asphalt to resist permanent deformation, the MSCR test is implemented with DSR.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that the penetration, ductility, and softening point are not able to characterize the rutting resistance performance index of asphalt under repeated vehicle loading [ 33 ]. In order to better evaluate the ability of asphalt to resist permanent deformation, the MSCR test is implemented with DSR.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the mechanical properties, especially toughness, of the bond coat should also be outstanding. Therefore, thermosetting epoxy-based bond coats have been widely utilized in the construction of steel bridges [ 22 , 23 , 24 ]. As an abbreviation denoting epoxy-modified asphalt, epoxy asphalt was initially developed for the pavement of airfields in the late 1950s [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, academician Wei Huang et al used epoxy-modified asphalt binder as a binder to prepare asphalt mixtures, which were successfully used in the deck-paving project of the Nanjing Yangtze River Second Bridge [ 16 ]. Since then, thermosetting epoxy-modified asphalt binder has been widely used as a paving material for steel box girder bridges worldwide, achieving better paving results [ 17 , 18 , 19 ]. Depending on the advantages of thermosetting epoxy-modified asphalt binder, a considerable amount of research work has been carried out on mixture performances in the laboratory to determine its potential engineering applications [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%